2017
DOI: 10.1016/j.metabol.2017.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Impaired calcium sensing distinguishes primary hyperparathyroidism (PHPT) patients with low bone mineral density

Abstract: Context A subset of PHPT patients exhibit a more severe disease phenotype characterized by bone loss, fractures, recurrent nephrolithiasis, and other dysfunctions, but the underlying reasons for this disparity in clinical presentation remain unknown. Objective We sought to identify new mechanistic indices that could inform more personalized management of PHPT. Design Pre-, peri-, and postoperative data and demographic, clinical, and pathological information from patients undergoing parathyroidectomy for PH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Tumors derived from PHPT patients with osteoporosis fell almost exclusively within Clusters 2 and 3, with only a single instance found in Cluster 1. The association between calcium-resistant tumor gene expression profiles and bone mineral density loss observed in this sample set provides molecular evidence supporting our earlier report of a link between tumor biochemical behavior and PHPT clinical presentation (Weber et al 2017).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Tumors derived from PHPT patients with osteoporosis fell almost exclusively within Clusters 2 and 3, with only a single instance found in Cluster 1. The association between calcium-resistant tumor gene expression profiles and bone mineral density loss observed in this sample set provides molecular evidence supporting our earlier report of a link between tumor biochemical behavior and PHPT clinical presentation (Weber et al 2017).…”
Section: Resultssupporting
confidence: 90%
“…Using this approach, we showed that parathyroid tumors exhibiting calcium resistance were strongly associated with reduced bone density in patients with sporadic, non-familial PHPT (Weber, et al 2017). The finding that attenuated calcium responsiveness in a subset of parathyroid tumors is selectively linked to clinically significant bone mineral density (BMD) loss suggests the existence of phenotypically distinct sub-classes of PHPT patients with differential disease courses and alternative underlying etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…This abnormal calcium or 1, 25-(OH) 2 D sensing in tumours along with autonomous PTH secretion can explain the lack of correlation between PTH and 25-OHD in our cohort. Impaired calcium sensing in parathyroid tumours was indeed observed in one subset of patients with severe bone mineral density de cit [20].…”
Section: Discussionmentioning
confidence: 96%
“…The primary target organ of PHPT is the kidney, which can develop into kidney stones[ 5 ]. It can also manifest as urinary calculi and osteolytic bone changes, as well as other systemic lesions[ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%